Criteria of talent in sport - Hohmann, A.; Dierks, B.; Luehnenschloss, D.; Seidel, I.; Wichmann, E.
The findins of the study led to three criteria, that are useful to identify talents in swimming: 1. The performance of the young swimmers in competition, which has to be understood as a gross indicator of the swimmers actual and overall ability. 2. The degree of utilization of different basic abilities, e.g. motor coordination, body constitution, and others on a certain level of performance. 3. The speed of development of the performance, that is the rates of gains in performance from year to year within the long run of the training process.